Mobile Phone Usage Pattern and its Impact on Society: A quantitative Analysis - Anwar, Naseem; Alam, Muhammad Kaqbad Alam; Moazam, Dr. Saniya Moazzam (Journal of Peace, Development and Communication, 2024)
As widely recognized, cell phones have become indispensable in modern life, owned by people of all ages. They facilitate a multitude of tasks and are accessible anytime, anywhere. Our study aimed to explore the societal impact of smartphones and their myriad features on real-life interactions. Understanding the relationship between smartphones and social interactions is crucial. The study involved a 12-question survey assessing cell phone ownership, daily usage patterns, and hours spent on smartphones. Twenty-six participants, evenly split between genders, were surveyed, and the data were visualized using pie charts. Our findings suggest that individuals aged 16 to 20 are most affected socially by cell phone usage. Younger participants tend to use smartphones more frequently than older ones, with entertainment being the primary use for the former and work/communication for the latter. Despite varied usage patterns, most individuals find that cell phones have simplified their lives. However, the production of mobile technology has led to concerns about overreliance, potentially limiting individuals’ cognitive abilities by substituting technology for mental challenges. Keywords: Mobile devices, technological advancements, emerging models, societal dynamics, everyday interactions